2011
DOI: 10.1038/nature10407
|View full text |Cite
|
Sign up to set email alerts
|

SUMO1-dependent modulation of SERCA2a in heart failure

Abstract: SR Ca2+ ATPase 2a (SERCA2a) is a critical ATPase responsible for Ca2+ re-uptake during excitation-contraction coupling. Impaired SR Ca2+ uptake resulting from decreased expression and reduced activity of SERCA2a is a hallmark of heart failure (HF)1. Accordingly, restoration of SERCA2a expression by gene transfer has proven to be effective in improving cardiac function in HF patients2 as well as in animal models3. The small ubiquitin-related modifier (SUMO) can be conjugated to lysine residues of target protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
357
2
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 337 publications
(367 citation statements)
references
References 32 publications
7
357
2
1
Order By: Relevance
“…A drug that acts like 2D12, preventing PLB binding to SERCA2a, might be expected to produce large increases in cardiac contraction and relaxation in failed human myocardium (9). Although not the focus of this study, in light of our current results, we feel it important to address the very recent study by Kho et al (30) in which it was suggested that SUMOylation of SERCA2a in human hearts by SUMO1 increases Ca 2ϩ pump stability and Ca 2ϩ -ATPase activity by enhancing ATP binding affinity (30). The authors also suggested that the level of SUMOylation of SERCA2a is reduced in failing human hearts and that restoration of SERCA2a SUMOylation may be a viable means of treating heart failure (30).…”
Section: Mechanism Of Plb Inhibition In Sr Vesicles-it Is Largelymentioning
confidence: 82%
See 1 more Smart Citation
“…A drug that acts like 2D12, preventing PLB binding to SERCA2a, might be expected to produce large increases in cardiac contraction and relaxation in failed human myocardium (9). Although not the focus of this study, in light of our current results, we feel it important to address the very recent study by Kho et al (30) in which it was suggested that SUMOylation of SERCA2a in human hearts by SUMO1 increases Ca 2ϩ pump stability and Ca 2ϩ -ATPase activity by enhancing ATP binding affinity (30). The authors also suggested that the level of SUMOylation of SERCA2a is reduced in failing human hearts and that restoration of SERCA2a SUMOylation may be a viable means of treating heart failure (30).…”
Section: Mechanism Of Plb Inhibition In Sr Vesicles-it Is Largelymentioning
confidence: 82%
“…Although not the focus of this study, in light of our current results, we feel it important to address the very recent study by Kho et al (30) in which it was suggested that SUMOylation of SERCA2a in human hearts by SUMO1 increases Ca 2ϩ pump stability and Ca 2ϩ -ATPase activity by enhancing ATP binding affinity (30). The authors also suggested that the level of SUMOylation of SERCA2a is reduced in failing human hearts and that restoration of SERCA2a SUMOylation may be a viable means of treating heart failure (30). However, in our present study with normal and failed human hearts, no 150-kDa mobility form that might correspond to SUMOylated SERCA2a was detected.…”
Section: Mechanism Of Plb Inhibition In Sr Vesicles-it Is Largelymentioning
confidence: 82%
“…Inhibition of MAO‐B results in reduced formation of H 2 O 2 and aldehydes, two molecules that are known to stimulate mitochondrial and myocardial damage 41. Furthermore, in context with oxidative stress, we also explored SUMO‐1 which has been found to be highly relevant in the response to cellular stress and rescues SERCA2a ATPase (cardiac isoform of sarcoplasmic reticulum calcium ATPase) activity in heart failure 42, 43. In the present study, we observed a trend towards elevation in SUMO‐1 relative protein levels both in the BZ and RR of RG‐treated group.…”
Section: Discussionmentioning
confidence: 99%
“…We next decided to explore the role of other degradation pathways responsible for stabilizing SERCA2a levels in response to progesterone treatment. A study by Kho et al (14) pointed to the involvement of Cells were stimulated with progesterone for 48 h, and cell lysates were immunoprecipitated with IgG (isotype-matching control antibody) and antiSERCA2a. Immune complexes were then separated on 10% SDS gels and subjected to Western blot analysis with antibody directed against total ubiquitin.…”
Section: Camentioning
confidence: 99%
“…Similarly, the pump function of SERCA2a is compromised by glutathiolation (1). More recently, it has been shown that SERCA2a expression and function are compromised in HF, in part by imbalance between SUMOylation and ubiquitination (14). Kho et al (14) demonstrate that SUMOylation of SERCA2a (addition of SUMO1 at lysine residues within the ATP-binding domain in SERCA2a) is a prerequisite for stability and pump activity.…”
mentioning
confidence: 99%